Energy Implications of Lot Sizing Decisions in Refrigerated Warehouses - Beatrice Marchi (Energies, 2020)
Cold supply chains (CSCs) are responsible for preserving the quality of perishable goods in storage and transport. They consume significant amounts of energy to maintain cooling temperatures constant over time continuously and ubiquitously, which is affected by the surrounding environment and the users’ behavior. The storage filling level is one specific feature of refrigerated warehouses observed in practice: they are more energy efficient when kept full of items, reducing the space that air occupies. Inventory management models that consider energy consumption have received increasing attention recently due to an increase in stakeholders’ awareness of sustainability. Despite this interest, there is no work that jointly considers the effects of the filling level and the temperature inside the warehouse. This study, therefore, integrates those aspects into the economic order quantity model and finds the optimal lot size quantity that minimizes the total system cost, which is the performance measure used herein. It provides numerical results and brings some insights into the behavior of the model proposed.